Lactation Persistency in Bulgarian Murrah Buffalo Cows - Penchev, P.; Peeva, Tz. (Journal of Buffalo Science, 2013)
With the objective to establish the lactation persistency and its variability as affected by different factors, the study assigned 953 lactations of 310 Bulgarian Murrah buffalo cows bred on the farm of Agricultural Institute – Shumen within the period 1967-2009. The main method of measurement was the mean post-peak milk yield reduction. The data were processed by the conventional statistical procedure, as well as by the software products LSMLMW and MIXMDL. The persistency of milk yield after reaching peak was established to be relatively high (89.22%). Its variance is to a great extent explained by the factors days in milk (P<0.001) and parity (P<0.001), defining favorable effect of increased lactation length, and adverse effect of advancement in lactation order. The significant effect of season of calving (P<0.001) is expressed in higher lactation persistency in the autumn and winter calvers. The other environmental factor, period, and the genetic factor (individual) are significant at P<0.01, while the effect of productivity level is not. The portion of the peak yield was estimated to be 15.75% of the lactation productivity, the percentage of the greatest yield drop – 11.38%, the persistency ratio between the first and second lactation half – 73.60%.